Ossification Vesicles with Calcium Phosphate in the Eyes of the Insect Copium teucrii (Hemiptera: Tingidae). (2011) - Garcia-Guinea, Javier; Jorge, Alberto; Tormo, Laura; Furio, Marta; Crespo-Feo, Elena; Correcher, Virgilio; Prado-Herrero, Pedro; Soria, Ana C.; Sanz, Jesus; Nieves-Aldrey, Jose L.
Abstract : Arthropod eyes are built of repeating units named ommatidia. Each single ommatidium unit contains a cluster of photoreceptor cells surrounded by support cells and pigment cells. The insect Copium eye ommatidia include additional calcium-phosphate deposits, not described in insects to date, which can be examined today using a combined set of modern microscopy and spectroscopy techniques. Teucrium gnaphalodes L'Her plants, growing in central Spain, develop galls induced by Copium insects. A survey of C. teucrii adult specimens resulted in surprising environmental scanning electron microscopy (ESEM) images, showing that their bright red eyes contain a calcium-phosphate mineralization. A complete survey of Copium eye specimens was performed by ESEM using energy-dispersive spectroscopy, backscattered electron detector and cathodoluminescence (CL) probes, field emission scanning electron microscopy, micro-Raman spectroscopy, and confocal laser scanning microscopy in order to learn ommatidia features, such as chemical composition, molecular structure, cell membrane, and internal ommatidium eye fluids and calcium-phosphate distribution deposits. The CL panchromatic images distinguish between the calcium-phosphate ommatidium and calcium-phosphate setae, which are more apatite rich. They show Raman bands attributable to bone tissue apatite biomaterials, such as bone, collagen, lipids, and blood, i.e., peptides, amide-S, amide-II, amide-III, and cytochrome P-450scc. The chemical composition of both galls and leaves of T. gnaphalodes was determined by gas chromatography – mass spectrometry (GC-MS) of their extracts. The spectrometric and microscopic images reveal that the calcium-phosphate mineralization is formed and constrained to Copium ommatidia, which are both matrix vesicles generating mixtures of apatite collagen and operational compound eyes of the insect.